The effect of labour migration and structural changes on economic development - O. Nosova (Вісник Харківського національного університету імені В.Н. Каразіна: Серія Економіка)
The article aims to analyze effects of the labour migration and structural changes on economic development. The Russian invasion in Ukraine increased geopolitical risks for the global economy in 2022 and in the present time. The most immediate economic impact of the Ukrainian conflict was sharply rising food, energy, and commodity prices in the world. In the process of massive population displacement people were forced to leave their homes and lose their livelihood. The analysis of basic approaches to the effects of labour migration, and structural changes on global development highlights the contemporary challenges for the current institutional and structural setting of the economies and societies. The current global crisis is likely to have deep-reaching effects that we cannot foresee. It has been mistaken to believe that migrants will serve as a safety valve for developed economies, by providing labour in times of expansion and going away in the recession (Castles & Vezzoli, 2009). The assessment of structural change on the inclusiveness and sustainability of socioeconomic development depends on the specific country. Both the relative supply of skills and skill-based technological change tends to increase income inequality, though not in all countries (Nomaler et al., 2021). The study of the impacts of international emigration on the evolution of the institutions in the origin countries demonstrates the influence of emigration per se (i.e., people who left the country can voice from abroad), and the transfer of the norms of the host country to the home country. The existence of both impacts was confirmed using different indicators of institutional quality. The effects appear stronger when skilled emigration is considered (Beine & Sekkat, 2013). It is proposed that new job structures based on hiring the low-cost labour will appear under the effects of increasing labour migration. One of the decisions could be adoption by policymakers of new systems of global migration governance based on international collaboration and the rule of law by taking lessons from the crisis experience. It will be directed to define sectors that can speed up the process of rebuilding the global economy. Diversifying the economy, increasing product/service sophistication, using comparative advantages and transfer of resources (both labour and capital) leads to more productive activities and a rise in well-being.